2023
DOI: 10.3390/molecules28041867
|View full text |Cite|
|
Sign up to set email alerts
|

CeO2-Supported TiO2−Pt Nanorod Composites as Efficient Catalysts for CO Oxidation

Abstract: Supported Pt-based catalysts have been identified as highly selective catalysts for CO oxidation, but their potential for applications has been hampered by the high cost and scarcity of Pt metals as well as aggregation problems at relatively high temperatures. In this work, nanorod structured (TiO2−Pt)/CeO2 catalysts with the addition of 0.3 at% Pt and different atomic ratios of Ti were prepared through a combined dealloying and calcination method. XRD, XPS, SEM, TEM, and STEM measurements were used to confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Moreover, for the P25-Pt sample, a weak diffraction peak at 2θ = 40.1, corresponding to the (111) plane, can be seen, indicating the presence of metallic platinum (card no. 1011107) 39 . A close-up of the XRD pattern confirming the additional peak originating from platinum is shown in Figure S2 in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for the P25-Pt sample, a weak diffraction peak at 2θ = 40.1, corresponding to the (111) plane, can be seen, indicating the presence of metallic platinum (card no. 1011107) 39 . A close-up of the XRD pattern confirming the additional peak originating from platinum is shown in Figure S2 in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for the P25-Pt sample, a weak diffraction peak at 2θ = 40.1, corresponding to the (111) plane, can be seen, indicating the presence of metallic platinum (card no. 1011107)39 . A close-up of the XRD pattern confirming the additional peak originating from platinum is shown in FigureS2in the Supplementary Materials.The presence of Pt NPs diffraction peaks in the diffraction pattern for P25-Pt suggests the effective deposition of nanocrystalline Pt particles on the material's surface, possibly organized in clusters large enough to give rise to characteristic diffraction signals of appreciable intensity.…”
mentioning
confidence: 99%
“…This led to the quenching of fluorescence. 56 Fig. S9 † showed that the fluorescence lifetime of 1@EtOH decayed to 0.33 ns after DMNA was added due to the PET mechanism.…”
Section: Sensing Properties Toward Dmnamentioning
confidence: 99%